Production and cleavage of Drosophila Hsp70 transcripts extending beyond the polyadenylation site. - Berger, S.L.; Meselson, M. (Nucleic Acids Research, 1994)
Transcription downstream of the polyadenylation site was studied in the Drosophila hsp70 gene, whose high level of transcription in response to temperature elevation facilitates detection of rare and possibly short-lived transcripts. Transcription downstream of the polyadenylation site was detected both in cultured cells and in intact animals. Even shortly after temperature elevation the extended nonpolyadenylated RNAs were rare relative to mature message, and their level continued to increase following temperature elevation even after the amount of mature message stopped increasing. The extended transcripts therefore are unlikely to be message precursors. Although continuous transcripts were detected extending as far as 2 kb downstream of the normal polyadenylation site, the predominant extended transcript was 0.45 kb long, apparently produced by cleavage of longer transcripts. Its amount relative to mature message increased with the duration and severity of heat-shock. As is the case in nonpolyadenylated histone mRNA, there is a potential stem-loop structure just upstream of the cleavage site. These data and other lines of evidence suggest that this extended transcript results from an alternative mode of stable 3'-end formation.